Korean Music Therapy Students’ Experience of Group Music Therapy: A Qualitative Case Study - So, Hyejin (Frontiers in Psychology, 2019)
The purpose of this qualitative case study is to describe the in-depth experiences of Korean students undergoing group music therapy. Seven students participated in eight consecutive weeks of group music therapy. The researcher collected and triangulated three data resources: individual interview transcripts, participant journals, and audiotaped sessions. The data were analyzed using the case study method and peer debriefing was conducted for trustworthiness. The four emergent themes and six categories were as follows: (1) Discovering one’s self (categories: what it means to be “me,” learning about self), (2) Inside group music therapy (categories: various responses to experiencing non-directive group, two different sides of experiencing silence, feeling a sense of safety and acceptance, sharing difficult experience with one’s own family), (3) Musical experience as a way to explore emotions, and (4) What learned through books became real. The results indicated that the student therapists’ experiences were linked to their personal development, unique experience of group music therapy dynamics, musical experience as an emotional container, and clinical development. Finally, it is recommended that cultural adaptations are made by providing both structure and space for Korean students to express themselves.